2005
DOI: 10.1161/01.cir.0000154900.76284.f6
|View full text |Cite
|
Sign up to set email alerts
|

Recommendations for Blood Pressure Measurement in Humans and Experimental Animals

Abstract: Abstract-Accurate measurement of blood pressure is essential to classify individuals, to ascertain blood pressure-related risk, and to guide management. The auscultatory technique with a trained observer and mercury sphygmomanometer continues to be the method of choice for measurement in the office, using the first and fifth phases of the Korotkoff sounds, including in pregnant women. The use of mercury is declining, and alternatives are needed. Aneroid devices are suitable, but they require frequent calibrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
739
3
43

Year Published

2007
2007
2018
2018

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 2,205 publications
(794 citation statements)
references
References 133 publications
9
739
3
43
Order By: Relevance
“…Although BP measurement every 15 to 30 minutes during asleep hours for ABPM was formally recommended in 2005,25 the adequacy has never been scientifically proved. In our simulation studies, we have demonstrated clearly that rate of STMS is less susceptible to measurement error than the amplitude by involving more BP measurements within the time frame between the nighttime trough and morning.…”
Section: Discussionmentioning
confidence: 99%
“…Although BP measurement every 15 to 30 minutes during asleep hours for ABPM was formally recommended in 2005,25 the adequacy has never been scientifically proved. In our simulation studies, we have demonstrated clearly that rate of STMS is less susceptible to measurement error than the amplitude by involving more BP measurements within the time frame between the nighttime trough and morning.…”
Section: Discussionmentioning
confidence: 99%
“…A more detailed description of the cohort stratification and the OFS design can be found in earlier reports (Bochud et al, 2005). Hypertension was diagnosed when subjects had a 24-hour SBP and/or DBP ≥135/85 mmHg (Pickering et al, 2005) or when they were on antihypertensive treatment. The prevalence of hypertension was 20% (males 22% and females 18%) with 2% of both genders on medication.…”
Section: Methods and Study Designmentioning
confidence: 99%
“…Weight will be measured with minimum clothing without shoes to the nearest 0.1 kg on a portable electronic weighing scale. Blood pressure will be measured twice using a standard instrument to the nearest 2 mm Hg [35]. Blood samples (5 mL: 1 mL-EDTA vial, 1 mL-Oxalate vial and 3 mL-plain vial) will be obtained to estimate haemoglobin, plasma glucose (mg/dL), total serum cholesterol (mg/dL), high-density lipoprotein (mg/dL), low-density lipoprotein (mg/dL) and triglycerides (mg/dL) using standard laboratory methods.…”
Section: Methodsmentioning
confidence: 99%